Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1007/bf02478380
|View full text |Cite
|
Sign up to set email alerts
|

Iron complexes in zeolites as a new model of methane monooxygenase

Abstract: Iron complexes in the ZSM-5 zeolite matrix (c~-centers) are shown to perform single-turnover cycles of methane oxidation to methanol at room temperature when nitrous oxide is used as a source of oxygen. The origin of carbon and oxygen in the product methanol was traced using ~3C and ~SO isotopes. Probable structure of c4-sites as well as mechanistic features of the reaction allow to consider this system as a first successful model of methane monooxygenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
123
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 14 publications
5
123
1
6
Order By: Relevance
“…2,3,4,5,6 It has been demonstrated that N 2 O-pretreated Fe-ZSM-5 will react with methane to form methoxide species, which can subsequently be hydrolyzed to produce methanol. 3,7,8,9,10,11 Fe-ZSM-5 has also been shown to be active for the oxidation of benzene to phenol using N 2 O as the oxidant. in Fe-ZSM-5 is strongly dependent on the structure of the parent ZSM-5 with evidence for both diferric m-oxo-bridged clusters and Fe 2 O 3 particles.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,5,6 It has been demonstrated that N 2 O-pretreated Fe-ZSM-5 will react with methane to form methoxide species, which can subsequently be hydrolyzed to produce methanol. 3,7,8,9,10,11 Fe-ZSM-5 has also been shown to be active for the oxidation of benzene to phenol using N 2 O as the oxidant. in Fe-ZSM-5 is strongly dependent on the structure of the parent ZSM-5 with evidence for both diferric m-oxo-bridged clusters and Fe 2 O 3 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Its activity has been demonstrated for the selective oxidation of benzene to phenol using N 2 O [1][2][3][4][5], the catalytic decomposition of N 2 O [6][7][8][9], and for the selective catalytic reduction of nitrogen oxides using hydrocarbons (HC-SCR) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Fe-framework substituted ZSM5, activated by calcination in vacuo or by steaming at high temperature, has shown remarkable activity towards the selective oxidation of benzene to phenol by N 2 O and towards the decomposition of N 2 O [1][2][3][4][5][6][7][8][9]. Studies by Ribera et al [5] and Ramírez et al [13], performed on Fe-framework substituted ZSM5, activated by steaming (∼ 0.6 Fe wt%), have shown that during the activation treatment different Fe species are formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Only most recently a fully catalytic process using O 2 to regenerate the active sites has been reported. 11 Interestingly, Cu-and Fe-sites in different zeolite structures are able to catalyze this reaction at low temperatures, [5][6][7][8][9][10] while similar active sites in other materials lead to less favorable properties. Therefore it is a natural assumption that not only the structure and stoichiometry, but also the confining environment of the active sites plays a critical role.…”
mentioning
confidence: 99%